MitraClip repair of right-sided atrioventricular valve in a patient with congenitally corrected transposition of the great arteries: a case report. Issue 1 (4th December 2021) - Lewis, Antonio; Hakemi, Emad; Lopez, David; Cubeddu, Robert J
Abstract: Background: Patients with congenitally corrected transposition of the great arteries (ccTGA) often develop tricuspid valve (systemic atrioventricular valve) dysfunction due to right ventricular overload and dilatation, but isolated mitral valve (MV) disease is rarely found. Isolated mitral (subpulmonic atrioventricular valve) interventions, specifically catheter-directed, have not been reported up to date. Case summary: A man with ccTGA is evaluated for dyspnoea. Multimodality imaging assessment confirmed severe right-sided MV regurgitation due to prolapse. In light of high surgical risk, a minimally invasive transcatheter MitraClip procedure was pursued. Discussion: To our knowledge, this is the first case of successful MV repair via percutaneous approach using MitraClip in a patient with ccTGA and biventricular failure. Our case illustrates the safety and feasibility of the edge-to-edge procedure in such a rare instance, but also the importance of multimodality imaging (both invasive and non-invasive) and the Heart Team approach when caring for these complex patients.